Human Resources Development Strategies in Overcoming the Shortage of Educators and Education Personel - Rita Nurhayati; Joko Sutarto; Barokah Isdaryanti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
Abstract: The purpose of this study is to analyze the human resource (HR) development strategies adopted by SD Negeri 1 Jlegong in response to an acute staff shortage. The school is hampered by significant human resource shortages, particularly the absence of two classroom teachers, one physical education teacher, and the crucial position of school janitor. As a result, the principal must assume teaching responsibilities, full-time teachers are assigned outside their primary areas of expertise, and cleaning duties are divided on a rotating basis between staff and students. Using descriptive qualitative methods, this study collected data through observation, interviews, and documentation. The findings reveal that SD Negeri 1 Jlegong addresses these shortages through internal staff empowerment, teacher collaboration, the expansion of the principal's dual role, and a picket system (a mandatory cleaning duty roster). While these solutions are effective in maintaining day-to-day school operations, they emphasize that they are not sustainable long-term solutions unless supported by new government policies for the recruitment of permanent teaching and non-teaching staff. Keywords: Human Resource Development, Teaching Staff, Education Personnel, School Management.